2004
DOI: 10.1253/circj.68.410
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Attenuates the Incidence of Silent Brain Lesions in Patients With Nonvalvular Atrial Fibrillation

Abstract: Background Abnormal findings, including silent cerebral infarction, are frequently observed by magnetic resonance imaging (MRI) in patients with nonvalvular atrial fibrillation (NVAF); however, the prevalence and prevention strategy for these lesions have not been extensively studied. In the present study the preventive effects of aspirin on silent ischemic lesions was investigated. Methods and Results Silent lesions were counted using cranial MRI performed in 78 neurologically normal adults with sinus rhythm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
2
17
0
3
Order By: Relevance
“…Because of their selection within patients referring to a cardiovascular prevention outpatient clinic, the control group presented a moderate to high cardiovascular risk profile. Interestingly, the prevalence of SCI in subjects with a similar cardiovascular risk profile in previous experiences ranges from 53% to 58%, similar to that reported in the present study (12,13,31).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Because of their selection within patients referring to a cardiovascular prevention outpatient clinic, the control group presented a moderate to high cardiovascular risk profile. Interestingly, the prevalence of SCI in subjects with a similar cardiovascular risk profile in previous experiences ranges from 53% to 58%, similar to that reported in the present study (12,13,31).…”
Section: Discussionsupporting
confidence: 91%
“…Few studies (9)(10)(11)(12)(13) have investigated the prevalence of SCI in patients with AF. The limited sample sizes, retrospective designs, and heterogeneity of patients and techniques (e.g.…”
Section: See Page 1998mentioning
confidence: 99%
“…Some indirect data regarding the influence of aspirin on SVD-related strokes can be found in the literature. Sato et al [15] found that aspirin may be effective in preventing small silent lesions, as demonstrated by MRI, in patients with non-valvular atrial fibrillation. Kapelle et al [16] examined vascular type of recurrent ischemic stroke in patients with supratentorial TIAs or non-disabling ischemic strokes who were treated with aspirin.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Moreover, it is well known that the incidence of clinical stroke is significantly higher in subjects with SLI than in those without.…”
mentioning
confidence: 99%